Melaleuca alternifolia essential oil for acne treatment - Santos, Ana Loula dos (2021)
Objective: Among the various essential oils, the essential oil of Melaleuca alternifolia stands out for its multiple biological activities, the main one being antimicrobial, which makes it an important element for facial treatments. That said, the goal of this study is to evaluate the effectiveness of Melaleuca alternifolia essential oil in treating acne. Methods: the work carried out is characterized as a systematic literature review. The bibliographic survey was carried out in the Pubmed, ScienceDirect, Lilacs and Medline databases. During the search stage, articles published in the period from 2011 to 2021, articles with primary data and available in English, Portuguese and Spanish were established as inclusion criteria. On the other hand, the exclusion criteria were: articles that presented incompatibility with the topic, duplication in the bases and review articles. Results: after searching the databases, applying the inclusion criteria and reading the title and abstract, ten articles were selected that met the eligibility requirements. The ten articles were read in full, with a refined analysis of their methodology and the main results. Final considerations: melaleuca oil has great potential in the treatment of acne due to its important antimicrobial activity, ability to reduce injuries, as well as helping wound healing. In addition, it has advantages in relation to the use of antibiotics due to the low impact on the development of resistance and susceptibility to antimicrobials. Despite there are studies about this oil´s pharmacological activities, more researches are essential to consolidate it.